Traditional Chinese Medication Qiliqiangxin attenuates cardiac remodeling after acute myocardial infarction in mice - Tao, Lichan (Sci Rep, 2015)
In a multicenter randomized double-blind study we demonstrated that Qiliqiangxin (QLQX), a traditional Chinese medicine, had a protective effect in heart failure patients. However, whether and via which mechanism QLQX attenuates cardiac remodeling after acute myocardial infarction (AMI) is still unclear. AMI was created by ligating the left anterior descending coronary artery in mice. Treating the mice in the initial 3 days after AMI with QLQX did not change infarct size. However, QLQX treatment ameliorated adverse cardiac remodeling 3 weeks after AMI including better preservation of cardiac function, decreased apoptosis and reduced fibrosis. Peroxisome proliferator-activated receptor-γ (PPARγ) was down-regulated in control animals after AMI and up-regulated by QLQX administration. Interestingly, expression of AKT, SAPK/JNK, and ERK was not altered by QLQX treatment. Inhibition of PPARγ reduced the beneficial effects of QLQX in AMI remodeling, whereas activation of PPARγ failed to provide additional improvement in the presence of QLQX, suggesting a key role for PPARγ in the effects of QLQX during cardiac remodeling after AMI. This study indicates that QLQX attenuates cardiac remodeling after AMI by increasing PPARγ levels. Taken together, QLQX warrants further investigation as as a therapeutic intervention to mitigate remodeling and heart failure after AMI.